Psychometric properties of the Hebrew version of brief mindful self-care scale: A translation and validation study - Nasra Abdelhadi; Irit Bluvstein; Ronit Kigli-Shemesh; Semyon Melnikov (PLoS ONE, 2025)
Background Mindful self-care (MSC) integrates mindfulness into daily routines to enhance physical, mental, and emotional well-being. MSC is vital for nurses due to the high-stress nature of their work, which often leads to burnout and compassion fatigue. The Brief Mindful Self-Care Scale (BMSCS) was developed to measure MSC across six domains. However, there is limited research on MSC in Israeli nurses, and no Hebrew version of the BMSCS has been validated. Objectives This study aimed to translate and validate the Hebrew version of the BMSCS and assess its psychometric properties among Israeli nurses. Methods A cross-sectional study was conducted with 845 nurses recruited via a convenience sample. The BMSCS was translated into Hebrew using forward and backward translation. Psychometric analyses included exploratory and confirmatory factor analyses (EFA and CFA), item discrimination, and internal consistency (Cronbach’s alpha). Data were analysed using R software. Results EFA using maximum likelihood estimation with Promax rotation revealed a six-factor solution accounting for 49% of the total variance. CFA results confirmed the model fit after excluding two low-loading items (PC2 and PC6), with goodness-of-fit indices meeting predefined criteria (e.g., RMSEA = 0.049, CFI = 0.949). The Cronbach’s alpha for the total scale was 0.87, with subscale reliability ranging from 0.70 to 0.89. Subscale correlations supported the internal structure. Conclusions The Hebrew BMSCS demonstrated strong psychometric properties, providing a reliable and structurally sound tool for assessing MSC in Israeli nurses. This instrument can guide interventions to enhance nurses’ well-being and inform future research in high-stress healthcare settings.